The Effectiveness of Learning to Write Drama Texts through Assisted Productive Creative Models Short Film Media and Short Story Text Product Media Based on Student Learning Style - Aulia, Rifa; Subyantoro Subyantoro; Mukh Doyin (Universitas Negeri Semarang, 2025)
Learning to write drama texts is a learning that requires students to develop creativity, critical thinking skills, and language skills. The objectives of this study are (1) to analyze the effectiveness of learning to write drama scripts through a productive creative model assisted by short film media based on learning styles in grade XI high school students, (2) to analyze the effectiveness of learning to write drama scripts through a productive creative model assisted by short story text product media based on learning style in grade XI high school students, (3) to analyze the differences in the effectiveness of learning to write drama scripts through creative models Productive with the help of short film media and short story text product media based on learning styles in grade XI high school students. The design of this study is a simple factorial design with two experimental groups. The sample of this study is the learning of drama text writing skills for students in grade XI of SMA N 1 Bantan and SMA N 2 Bantan. The results of this study are (1) learning to write drama texts with a productive creative model assisted by short film media is more effective in students with an auditory learning style, (2) learning to write drama texts with a productive creative model assisted by short story text product media is more effective in students with a visual learning style, (3) learning to write drama texts with a productive creative model is more effective using short film media based on auditorial learning style. The findings in the research show that learning to write drama texts with a productive creative model is effective in using short film media based on auditory learning styles rather than short story text media based on students' learning styles. This research can be used to improve the quality of education and the quality of Indonesian learning.